Ecommerce Adoption and MSME Business Performance in Indonesia: Systematic Literature Review - Alfi Rahmawati; Tasya Kamila Hamdani; Wahyu Budi Priatna (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia's economy, yet the adoption rate of e-commerce among these businesses remains low. This study aims to identify the factors influencing e-commerce adoption among Indonesian MSMEs using the Technology-Organization-Environment (TOE) framework and to analyze its impact on business performance. A Systematic Literature Review (SLR) approach was applied to 23 scholarly articles published between 2013 and 2024. The findings indicate that technological factors (perceived usefulness, relative advantage, compatibility, security), organizational factors (organizational readiness, top management support, organizational culture, organizational size), and environmental factors (government support, competitive pressure, IT vendor support) significantly influence e-commerce adoption by MSMEs. Furthermore, e-commerce adoption has been proven to enhance MSMEs’ business performance in terms of increased sales, market reach, operational efficiency, and financial outcomes. This study highlights the importance of an integrative strategy involving the government, MSME actors, and technology providers to accelerate the digital transformation of the MSME sector in Indonesia